Study of hematological parameters among newborns with perinatal asphyxia - Dr. Sunita Koreti; Dr. Gunvant Singh Eske; Dr. Ajay Gaur; Dr. Akriti Gupta (Pediatric Review: International Journal of Pediatric Research, 2018)
The aim of this original research article was to identify the blood parameters as predictors of perinatal asphyxia and its correlation with severity of asphyxia.Setting: Postnatal Wards and Sick newborn unit of Pediatric Department, Kamla Raja, Gwalior.Design: A prospective case control study.Participants: 100 cases and 100 controls enrolled based on the selection criteria, on day 1 of life.Methods: On day 1of delivery newborns were enrolled, who fulfilled the inclusion criteria. Complete history, physical examination and neurological signs were recorded on a predesigned proforma. Hypoxic ischemic encephalopathy (HIE) Staging done. Cord blood samples were collected on day 1 and results analyzed.Results: The present study included 100 cases and 100 controls. Out of the total 100 cases, 23% (23) were HIE stage-I, 46% (46) were stage-II and 31% (31) were of stage –III Significant difference is seen in mean values of nucleated RBCs among the cases and controls (p value <0.001). It was 10.85 ± 6.39 and 5.91 ± 3.60 among cases and controls respectively. Leucocyte count was found 17.06 ± 7 among cases while among controls mean was 14.14 ± 4.15, which was significant. Similarly, significant difference was found in mean Hb among cases and control group. Polychromatophilia was found significant (p value <0.001) when compared between cases and controls and among cases themselves. The value of Positive predictive Value and Negative Predictive Value are maximum for n-RBCs. Accuracy for determining the mortality is also maximum. It is seen that area AUC for n-RBCs is maximum i.e. 0.795 which makes it the best blood parameter which correlates with mortality.Conclusions: Blood parameters are altered in perinatal asphyxia and can be used to predict the severity and outcome.